PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP PRESTASI KERJA DAN KEPUASAN KERJA DENGAN JOB RELEVANT INFORMATION SEBAGAI VARIABEL INTERVENING - ., Sabaruddinsah (Fakultas Ekonomi Universitas Islam 45, 2009)
The objective of teh study is to examine, job relevant information (JRI) as an intervening variable between budget participation with job performance and job satisfaction on west java municipalitity, JRI as an intervening variable is important in budgeting system due to its predictive power on budget formulation, The sample of this study is all the staff with in charge in buger formulation in west java province institutions, This study used instruments which are developed Milani (1975), Miller (1999), Josep M, Larkin (1990) and Kren (1992), The period of collecting questionnairce is between oktober dan november 2008, This study distributed 255 questionnaires to all municipalitity under west java province. There were 70 questionnaires which returned and due to the feasibility of questionnaire, only 56 questionnaires. Used in further study. This study used path analysis to tes hypotesis. The result of the study supported HI and H2 which is indicated that there is positively significant between budget budget participation with job performance and job satisfaction. The study is also supported H3 and H4 which is indicated that JRI as an intervening variable between budget budget participation with job performance and job satisfaction.